UnIC: Towards Unmanned Intelligent Cluster and Its Integration into Society. (May 2022) - Zhang, Fubiao; Yu, Jing; Lin, Defu; Zhang, Jun
Graphical abstract: Highlights: Collaborative unmanned systems have emerged to meet our society's wide-ranging grand challenges, with their advantages including high performance, efficiency, flexibility, and inherent resilience. Increasing levels of group/team autonomy have been achieved due to the embodiment of artificial intelligence. The current networked unmanned systems are primarily designed for and applicable to a narrow range of domain-specific missions. The current networked unmanned systems do not have sufficient human-level intelligence and human needs fulfillment for the challenging missions in our lives. We propose a vision of human-centric networked unmanned systems: Unmanned Intelligent Cluster (UnIC). Within this vision, distributed unmanned systems and humans are connected via knowledge sharing and social awareness to achieve collaborative cognition. This paper details UnIC's concept, sources of intelligence, layered architecture, and reviews enabling technologies for achieving this vision. In addition to the technological aspects, the social acceptance issues are highlighted. Abstract: Collaborative unmanned systems have emerged to meet our society's wide-ranging grand challenges, with their advantages including high performance, efficiency, flexibility, and inherent resilience. Increasing levels of group/team autonomy have also been achieved due to the embodiment of artificial intelligence (AI). However, the current networked unmanned systems are primarily designed for and applicable to a narrow range of domain-specific missions, and do not have sufficient human-level intelligence and human needs fulfillment for the challenging missions in our lives. We propose in this paper a vision of human-centric networked unmanned systems: Unmanned Intelligent Cluster (UnIC). Within this vision, distributed unmanned systems and humans are connected via knowledge sharing and social awareness to achieve collaborative cognition. This paper details UnIC's concept, sources of intelligence, and layered architecture, and reviews enabling technologies for achieving this vision. In addition to the technological aspects, the social acceptance issues are highlighted.